Modelling the Accessibility Classification of Railway Lines: A case study of Northeast China railway network - Yang, Mian; Wang, Y.J. (Promet - Traffic&Transportation, 2013)
A major problem addressed in railway network planning relates to distinguishing the role of the railway line in the network, and making a reasonable classification of the lines based on their role. Accessibility has been widely used to measure the role of transportation infrastructure in various studies, but few quantitative models for the classification of the role have been presented yet. In this paper, the line accessibility classification model is proposed, which aims to distinguish the role of railway lines in the network and to classify the lines into different grades. The practicability of the model is demonstrated through the case study of Northeast China railway network where the railway lines in Northeast China can be classified into three grades. The line accessibility classification model is supposed to be a strategic decision support tool for planners and policy makers to determine the classification of railway lines.